Comparison of Some Statistical Measurements Extracted From Benign, Malignant and Normal MRI Brain Images - Adnan Omar, Raid; Mohammed Najim, Jassim; H Abood, Imad (Iraqi Journal of Science, 2021)
People may believe that tissue of normal brain and brain with benign tumorhave the same statistical descriptive measurements that are significantly differentfrom the of brain with malignant tumor. Thirty brain tumor images were collectedfrom thirty patients with different complains (10 normal brain images, 10 imageswith benign brain tumor and 10 images with malignant brain tumor). Pixelintensities are significantly different for all three types of images and the F-test wasmeasured and found equal to 25.55 with p-value less than 0.0001. The means ofstandard deviations and coefficients of variation showed that pixel intensities fromnormal and benign tumors images are almost have the same behavior whereas theywere significantly different from images of malignant brain tumors with F-testsequal to 23.22 and 6.51 respectively with corresponding p-values of 0.00001 and0.005 respectively.